Pelatihan Komputer Sebagai Upaya Meningkatkan Kompetensi Kerja Kelompok Masyarakat Pada LKP Ivan Private Course Pematangsiantar - Hendry Qurniawan; Ika Purnama Sari; Ilham Syahputra Saragih (Al-Umm: Jurnal Pengabdian dan Pengembangan Masyarakat, 2026)
In this digital era, all groups are required to be able to keep up with the times. The development of information technology is now able to change the competency needs of the workforce in various sectors. Mastery of computers and office applications is one of the basic skills that must be possessed by all people in increasing competitiveness in the world of work, but there are still several groups of people who still have limitations in operating computers, especially in Microsoft Office applications and also the use of the internet as a means of supporting productivity. This is also found in community groups who are partners in activities at LKP Ivan Private Course Pematangsiantar. Therefore, this Community Service activity aims to improve the work competency of participants through computer training activities. The implementation method carried out in this activity consists of several stages, starting from identifying partner needs, preparing training models, implementing training, mentoring and also evaluation. This training is carried out through participatory activities so that participants gain new experiences. The results of this Community Service activity show an increase in knowledge, skills and also self-confidence in participants. Participants are also able to use Microsoft Office applications, make presentations and utilize technology. This activity has had a significant positive impact on all members of the community. Through this activity, participants are able to increase their opportunities for employment or develop independent businesses